Necroptosis Inhibition by Hydrogen Sulfide Alleviated Hypoxia-Induced Cardiac Fibroblasts Proliferation via Sirtuin 3 - Yue Zhang (MDPI AG, 2021)
Myocardial ischemia or hypoxia can induce myocardial fibroblast proliferation and myocardial fibrosis. Hydrogen sulfide (H2S) is a gasotransmitter with multiple physiological functions. In our present study, primary cardiac fibroblasts were incubated with H2S donor sodium hydrosulfide (NaHS, 50 μM) for 4 h followed by hypoxia stimulation (containing 5% CO2 and 1% O2) for 4 h. Then, the preventive effects on cardiac fibroblast proliferation and the possible mechanisms were investigated. Our results showed that NaHS reduced the cardiac fibroblast number, decreased the hydroxyproline content; inhibited the EdU positive ratio; and down-regulated the expressions of α-smooth muscle actin (α-SMA), the antigen identified by monoclonal antibody Ki67 (Ki67), proliferating cell nuclear antigen (PCNA), collagen I, and collagen III, suggesting that hypoxia-induced cardiac fibroblasts proliferation was suppressed by NaHS. NaHS improved the mitochondrial membrane potential and attenuated oxidative stress, and inhibited dynamin-related protein 1 (DRP1), but enhanced optic atrophy protein 1 (OPA1) expression. NaHS down-regulated receptor interacting protein kinase 1 (RIPK1) and RIPK3 expression, suggesting that necroptosis was alleviated. NaHS increased the sirtuin 3 (SIRT3) expressions in hypoxia-induced cardiac fibroblasts. Moreover, after SIRT3 siRNA transfection, the inhibitory effects on cardiac fibroblast proliferation, oxidative stress, and necroptosis were weakened. In summary, necroptosis inhibition by exogenous H2S alleviated hypoxia-induced cardiac fibroblast proliferation via SIRT3.